PENGARUH E-WOM TERHADAP CITRA PERUSAHAAN DAN DAMPAKNYA TERHADAP NIAT BELI KONSUMEN PADA SITUS ONLINE SHOPEE. ID - Sri Rahmi, Rizki Amalia (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
Abstract: This study aims to determine the effect of electronic word of mouth on corporate image and its impact on purchase intention. The sampling technique used is accidential sampling, with a sample of 100 respondentd. Analytical techniques in this study using path analysis and the sobel. The result showed that electronic word of mouth has a significant effect on corporate image and its impact on purchase intention.Keywords: Electronic Word of Mouth, Corporate Image And Buying Intention.